Orbitozygomatic approach for bullet retrieval from the temporal fossa. Issue 3 (3rd July 2019) - Cho, Su Min; Cho, David; Read-Fuller, Andrew; Vrcek, Ivan
Abstract: Gunshot wounds involving the periorbital region pose numerous challenges due to the high morbidity related to direct and collateral ophthalmic injury. Additionally, the critical structures of the orbit are often injured, resulting in a variety of serious sequelae. The technique for bullet retrieval is also a special concern, given the limited space in the orbit and presence of critical structures. We present a 34-year-old woman who received a gunshot wound through the right orbit, with the main bullet fragment lodging itself at the junction of the anteroinferior temporalis fossa and the skull base. We retrieved the fragment through an orbitozygomatic approach, where we dissected posterolaterally through the superior orbital fissure to reach the temporal fossa. Several smaller bullet fragments were also extracted along the way to the temporal fossa. The orbitozygomatic approach was particularly useful in this case due to the nature of the gunshot wound where the bullet had traversed through the globe and orbit to the temporal fossa. This approach avoided the need for a direct incision, which avoided potential frontal branch injury and further temporalis muscle trauma. It also provided a means to seal the small cerebral spinal fluid leak.